2018
DOI: 10.1021/acs.langmuir.8b00480
|View full text |Cite
|
Sign up to set email alerts
|

Nanodroplets Impact on Rough Surfaces: A Simulation and Theoretical Study

Abstract: Impact of droplets is widespread in life, and modulating the dynamics of impinging droplets is a significant problem in production. However, on textured surfaces, the micromorphologic change and mechanism of impinging nanodroplets are not well-understood; furthermore, the accuracy of the theoretical model for nanodroplets needs to be improved. Here, considering the great challenge of conducting experiments on nanodroplets, a molecular dynamics simulation is performed to visualize the impact process of nanodrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…The vast majority of computer simulations of the aforementioned systems deal with molecular dynamics, and some employ the method of Monte Carlo. , Most of the tasks studied can be divided into two classes: simulations of droplets of “pure” (one-component) liquids ,,, and those formed by multicomponent liquids. ,,, For the pure liquids, the studies mainly dealt with evaporation of the droplets under different conditions. It is also worth mentioning simulations of droplets’ motion ,,, because physical processes in the droplets caused by their motion are difficult to register in experiments. For example, Gao et al demonstrated that nanodroplets could bounce when they collide with textured surfaces or when two nanodroplets coalesce on the textured surfaces. , The field of the multicomponent droplets is much less developed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The vast majority of computer simulations of the aforementioned systems deal with molecular dynamics, and some employ the method of Monte Carlo. , Most of the tasks studied can be divided into two classes: simulations of droplets of “pure” (one-component) liquids ,,, and those formed by multicomponent liquids. ,,, For the pure liquids, the studies mainly dealt with evaporation of the droplets under different conditions. It is also worth mentioning simulations of droplets’ motion ,,, because physical processes in the droplets caused by their motion are difficult to register in experiments. For example, Gao et al demonstrated that nanodroplets could bounce when they collide with textured surfaces or when two nanodroplets coalesce on the textured surfaces. , The field of the multicomponent droplets is much less developed.…”
Section: Introductionmentioning
confidence: 99%
“…It is also worth mentioning simulations of droplets’ motion ,,, because physical processes in the droplets caused by their motion are difficult to register in experiments. For example, Gao et al demonstrated that nanodroplets could bounce when they collide with textured surfaces or when two nanodroplets coalesce on the textured surfaces. , The field of the multicomponent droplets is much less developed. In particular, there are no computer simulations of nanodroplets of polymer solutions and structures formed after solvent evaporation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Koplik et al [14] employed MD to study the impact of nanodroplets of Lennard-Jones liquids, and observed various phenomena including stick, bounce, splash, and disintegrate, depending on the initial velocity and composition of droplets. Koishi et al [29] and Gao et al [30] used MD to study the bouncing performance of nanodroplets on columnar array structures, with a focus to develop the theories and models on the spreading dynamics and energy transformation, without the consideration of the contact time. Li et al [31] investigated the effect of nanoridges on reducing liquid-solid contact time.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, its modeling for the viscous dissipation characterization becomes particular of concern to many studies. 21,22,36,38,39 The main models based on the energy balance approach are summarized in the second part of We…”
mentioning
confidence: 99%